Determining the type of bond between diatomic cluster of platinum and hydrogen: quantum mechanical approach - M.A. Miswan,; M.M. Anas,; G. Gopir, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Type of bond is vital to understand the mechanism of interaction between corresponds atoms. We used three kinds of method to determine the type of bond between diatomic cluster of platinum and hydrogen: types of element, electronegativity and electron distribution. In this work, we found that the results from these three methods are not unanimously agreed with each other for bond type forming in platinum-hydrogen diatomic cluster. Thus, we conclude that the type of bond is hybrid of both: mainly covalent and slightly ionic.